McLuhan and Debray – theoretical (dis)harmony - Vučković, Branislava (Sociološki pregled, 2021)
The subject of this paper is a comparative presentation of certain aspects of theoretical views of communication between two researchers with a very different academic background, Marshall McLuhan and Régis Debray. Starting from the hypothesis that, to the extent that their research interests overlap, the conclusions reached are related or at least complementary, our goal is to identify, on the one hand, possible links, which would in some way represent additional confirmation of the value of their theories, and on the other hand, what are the dividing lines that drive Debray to a kind of “clash” with McLuhan. By applying the basic scientific methods of analysis and deduction to their theoretical concepts, and their comparison, we found that the intersection of the two theories represents the emphasized role of technology in the processes of cultural dynamics.
Keywords: Marshall McLuhan; Régis Debray; communication; culture; technology